2012
DOI: 10.1097/olq.0b013e318265b180
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of HIV/STIs and Associated Factors Among Men Who Have Sex With Men in An Giang, Vietnam

Abstract: Although prevalence levels are lower in An Giang, Vietnam than in some other comparable locations, HIV/sexually transmitted infections prevention, and sexual health promotion targeting MSM are highly important in this location.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 18 publications
2
34
2
1
Order By: Relevance
“…All sample demographic characteristics have been reported previously 4. In brief, 73.2% of respondents were below 25 years of age, 36.6% reported completion of primary education or were illiterate, 7.9% had ever-married a woman, and 40.4% did not self-identify as gay.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All sample demographic characteristics have been reported previously 4. In brief, 73.2% of respondents were below 25 years of age, 36.6% reported completion of primary education or were illiterate, 7.9% had ever-married a woman, and 40.4% did not self-identify as gay.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with their transgender/gay-identified counterparts, ‘straight’ MSM who do not identify as gay are less likely to test for HIV despite higher infection risks 4. This suggests that most HIV-infected ‘straight’ MSM may not be aware of their infection, representing a substantial risk of HIV transmission to their female partners.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7] Rectal CT and NG infections are associated with an increased risk of HIV acquisition in men, possibly due to mucosal inflammation and recruitment of HIV-susceptible lymphocytes to local tissue sites. [8][9][10] Men with urethral CT or NG infection may also have higher seminal plasma HIV viral loads and may therefore be more likely to transmit HIV to a sexual partner during insertive anal intercourse.…”
mentioning
confidence: 99%
“…A study from Vietnam reported the prevalence of HIV, syphilis, gonorrhea, chlamydia, and gonorrhea/chlamydia to be 6.3%, 1.3%, 1.8%, 3.2%, and 4.7%, respectively [14]. Meanwhile, in a community based study in Honk Kong, Wong et al found that the prevalence of HIV, gonorrhea and chlamydia was found to be 3.6%, 0.2% and 4.7%, respectively [15].…”
Section: Discussionmentioning
confidence: 94%